ChemInform Abstract: C3‐Symmetric Chiral Trisimidazoline‐Catalyzed Friedel—Crafts (FC)‐Type Reaction. Issue 2 (January 2015) - Takizawa, Shinobu; Hirata, Shuichi; Murai, Kenichi; Fujioka, Hiromichi; Sasai, Hiroaki
Abstract The first imidazoline‐mediated highly enantioselective Friedel—Crafts‐type reaction between aldimines and naphthols is reported.